Two new species of Eutardigrada from Victoria Land, Antarctica - Pilato, Giovanni; Sabella, Giorgio; D’urso, Vera; Lisi, Oscar (Zootaxa, 2017)
Two new species are recorded from Victoria Land (Antarctica): Mixibius felix sp. nov. and Milnesium validum sp. nov. A third species, Diphascon sanae Dastych, Ryan & Watkins, 1990, is a new report for this region of the Antarctic continent. Mixibius felix sp. nov. has a smooth cuticle, eyes present, bucco-pharyngeal apparatus of the Mixibius type (rigid buccal tube without ventral lamina and with hook-shaped asymmetrical apophyses for the insertion of the stylet muscles); stylet supports inserted on the buccal tube at 65.7–68.0% of its length; pharyngeal bulb with apophyses and two macroplacoids; microplacoid and septulum absent; as is characteristic of the genus, the external claws are of Isohypsibius type and the internal are a modified Isohypsibius type. Milnesium validum sp. nov. has smooth cuticle; eye spots present; six triangular peribuccal lamellae with basal stripes; stylet supports inserted on the cylindrical buccal tube at 61.1–64.8% of its length; claw configuration [3-3]-[3-3] (i.e. all secondary claws with three points); secondary claws stout, with distal portion clearly wider than the basal portion and each with a rounded basal thickening (lunule); primary claws with accessory points; a long cuticular bar present under claws I–III. Adding the three above mentioned species, the list of species present in Victoria Land rises from 12 to 15; 11 of these are recorded exclusively to this region of the Antarctic continent.